Low-dose Radiation Improves Tumor Immune Microenvironment, Enhancing the Effects of Anti-CTLA-4 Therapy - Dong, Jigang; Qi, Ying; Sha, Sha (Iranian journal of immunology, 2025)
Radiotherapy destroys tumor cells primarily through direct DNA damage by high-energy particles or indirect DNA damage by free radicals. High-dose radiotherapy (HDR) destroys tumor cells while also damaging normal cells and may potentially cause immunosuppression. The effect of low-dose radiotherapy (LDR) on the tumor microenvironment (TME) may differ from those of HDR. To determine if combining low-dose radiotherapy with immune checkpoint inhibitors results in synergistic effects. We established a mouse model for lung cancer and categorized mice into 4 cohorts: NC (negative control) cohort, LDR cohort, anti-CTLA-4 cohort, and LDR+anti-CTLA-4 cohort. Changes in tumor volume were observed in each group, with particular attention given to the variations in immune cells and cytokines within the mouse tumors following LDR. The mice in the LDR+anti-CTLA-4 group exhibited the slowest growth in tumor volume, and low-dose radiotherapy tended to inhibit tumor growth. The proportion of infiltrating CD8+T cells increased and the proportion of infiltrating Treg cells decreased in the tumor after LDR. The levels of interferon (IFN) and the chemokines CXCL9, CXCL10 and CXCL11 were increased after low-dose radiotherapy. LDR has the ability to alter the immune microenvironment of tumors by promoting the production of IFN. Additionally, when combined with anti-CTLA-4, whole-body LDR can effectively suppress tumor growth in mice. The finding is of potential clinical significance and deserves further exploration.